Redesigning a Schwartz Center Rounds LibGuide to Support Compassionate Health Care. Issue 3 (3rd July 2021) - Rodriguez, Joy; Macias, Ana M.; Aiello, Marina T.
ABSTRACT: A team of Kaiser Permanente hospital librarians redesigned an existing Schwartz Center Rounds (SCR) LibGuide to provide an improved level of support to local medical center Schwartz Center Rounds Committees. The updated LibGuide provided easier navigation and greater visibility of content related to current and past topics. The redesign process also included creating a template for librarians to use to create a LibGuide for their local Schwartz Center rounds Committee. This provided librarians with a basic framework for creating a guide customized to their local medical center SCR Committee, plus allowed each librarian to maintain and add additional content to their respective guides as needed. Due to the COVID-19 pandemic in 2020, the guide was expanded to support SCR in an online environment by highlighting virtual library services and electronic resources.